Хот суурин газрын усны нөөцийн нэгдсэн менежментийн үнэлгээ: Чиг хандлага ба нөлөөллийн тогтолцоо - Тайванбат, Б.; Алтансүх, О.; Энх-Үүр, М.; Van Leeuwen, K.; Koop, Steven H. A. (Mongolian Journal of Engineering and Applied Sciences, 2020)
The large number of people living together in urban areas requires a comprehensive solutions for issues such as the reasonable allocation and adequate use of natural resources, urban planning, and efficient waste management to meet the city's needs. One of the main factors influencing the health and comfort of urban residents is the supply of clean water and sewerage systems. Therefore, in order to rationally allocate and use water resources to meet urban needs, and to create a healthy and comfortable living environment for city residents, it is necessary to develop an integrated water resources management plan at the national and basin levels, as well as an integrated water management plan and assessment for city level. In addition to assessing the current state of water management, it is important to identify factors and trends that may further strain water resources to prevent future risks. To address the pressures on water management in Ulaanbaatar and Darkhan, representing Mongolia's urban areas, the City Blueprint Approach, developed by the EU Water Innovation Partnership and the Dutch Institute of Water Cycle, was used in this study. Currently, this approach is used in about 80 cities in more than 40 countries, it is a relatively new and innovative method among Asian cities. As a result, water management in Ulaanbaatar and Darkhan is hampered by both social, economic, and environmental factors.